Diversity of Grasses, Seasonal Variations and Ecological Status of Grasslands in Jabalpur, Madhya Pradesh - Kunhikannan, C. (Indian Forester, 2008)
The graminaceous flora of Jabalpur district is represented by 121 species belonging to 67 genera. Among them, occurrence of Arthraxon quartinianus (A.Rich.) Nash, Elytrophorus spicatus (Willd.) A.Camus, Eulaliopsis binata (Retz.) Hubb., Heteropogon triticeus (R.Br.) Stapf ex Craib, Microchloa indica (L.f.) P.Beauv., Oropetium thomaeum (L.f.) Trin., Perotis indica (L.) Kuntze, Tragus roxburghii Panigrahi, is rare. The study revealed that various biotic and edaphic factors play an important role in determining the composition of grasses and modifying their sequence of appearance. Most of the grasslands were subjected to constant pressure of grazing and burning, and therefore did not reach the climax form in response to climate. However, in certain protected pockets, they developed into main type- Sehima- Dichanthium, while in the disturbed areas they were replaced by various subtypes like Sehima-Dichanthium, Chrysopogon-Bothriochloa and Aristida-Eragrostis subtypes, depending on the degree of disturbance. Grasses have major ecological role in reclamation of an area, owing to their fast regenerating capacity, tolerance to drought and arid conditions.